Evaluating Touch-Based Interactions in an Image Search Task - Gonzalez-Ibanez, R; Varela-Otarola, J; Barrera-Pulgar, C (Association for Computing Machinery, Inc, 2016)
Current technologies provide users different ways to interact with digital content, nevertheless, a physical gap between these two interaction components exists. In particular, touch-based interfaces enable users to use their own fingers to manipulate and interact with digital objects in a more direct fashion than mousebased interactions. However, it is not clear yet to what extent, if any, this type of interaction could help bridge the gap between users and the digital world in particular information-related contexts such as information search. In this paper we report preliminary results of a user study designed to compare mouse and touch-based interactions in the context of an image search task. This study is part of a larger research project focused on immersive interaction with digital information objects. Our results show that in spite of the novelty, high adoption rates, and tangible nature of touch-based interfaces, no significant differences exist with prevalent technology (i.e., mouse) in terms of performance; nevertheless, user experience was found to better in touch-based interactions. © 2016 ACM.